A Development of a Security System and Centralized Authentication for Souphanouvong University’s WiFi Network Using Protocol 802.1x and Radius - KITTIKHOUN, sangviane; MEKTHANAVANH, Vinath; SIMMAVONG, Soutthava; KOUNLAXAY, Kalaphath; SOUKCHALEUN, Sayxavath (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This research aims to address the inefficiencies in network access control and unequal bandwidth distribution within Souphanouvong University's WiFi network (SUWIFI). The study implemented a centralised authentication and security system using the IEEE 802.1x protocol, a RADIUS server (MikroTik User Manager), and the EAP-TTLS mechanism. The methodology included network topology redesign, centralised database integration, and traffic management using Simple Queues across various user groups. The results demonstrated a significant improvement in network stability and bandwidth allocation. Bandwidth was successfully optimised and limited to 6 Mbps per user, reliably accommodating an average of 150 concurrent users without network congestion. Furthermore, the centralised approach provided robust security against unauthorised access and streamlined administrative tasks. In conclusion, the integration of 802.1x and MikroTik-based RADIUS provides a scalable, secure, and highly efficient network management solution for the university environment.